Influence of organizational communication and organizational culture on employee performance among Secondary School Regulatory Agencies in Rivers State, Nigeria - Abd Aziz, Mohd Faiq; Musa, Siti Nur Syuhada; Owunna, Royal; Ajobi, Alice Omoefe (Human Resource Management Academic Research Society, 2024)
The study examined the influence of organizational communication and organizational culture on employee performance among secondary school regulatory agencies in Rivers State, Nigeria the study is quantitative and employed the stratified random sampling technique and simple random sampling to sample employees in agencies across four local councils with a sample size of 120 correspondents for the study. The study used an online Google form for data collection and was analyzed using the statistical tool (SPSS 25.0). The study discovered that organizational communication has a high-level significance, and while organizational culture has a medium level of significant effect on employee performance among the regulatory agencies.